Efektifitas Fraksinasi Kering pada Pengolahan Empulur Sagu dan Pemanfaatan Produk untuk Produksi Etanol - Abdurachman abdurachman; Erliza Noor; Titi Chandra Sunarti; Tajuddin Bantacut; Agus Eko Tjahjono; Musa Musa (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
Starch is more easily converted to sugars and fermented into ethanol. To increase ethanol productivity, a high-gravity fermentation method was developed. Sago trees are starch-producing that do not compete with food crops, but conventional processing has a negative impact on the environment. An alternative technology to minimize environmental impact is dry fractionation, product characteristics are suitable for ethanol production. Analysis of the effectiveness the processing of sago pith and the use of products for ethanol has never been published, so the analysis is carried out based on vertical differences in stem parts and determination of the optimum conditions of the ethanol production using sago starch-rich flour. Yield, starch recovery, starch ennrichment and shift starch are observational variables for the analysis of dry fractionation effectiveness. Starch-rich flour from the results of dry fractionation of each group of stem parts is mixed with a uniform composition and used as a fermentation medium. The one factor at a time (OFAT) experiment design was used to determine the effect of variables on optimal response, and verification is carried out. The distribution of starch granule size, starch content and parenchyma fiber characteristics can affect the effectiveness . Ethanol productivity showed optimum results at liquifaction 80oC for 60 minutes, using simultaneous saccharification and fermentation (SSF), high gravity fermentation and self-flocating yeast. The application of dry fractionation technology to obtain ethanol raw materials from sago trees has the potential to increase the added value of sago cultivation and the economic value of ethanol to be more competitive.